Assessing the Implementation of the Energy Management System in the First ISO 50001 Building in Indonesia - Kurniawan, Robi; Feinnudin, Agung (Purnomo Yusgiantoro Center, 2021)
This study focuses on the public building in Indonesia that has implemented an energy management system compliant with ISO 50001 standard. The main objectives of this study are to review the implementation of the energy management system in the building, highlighting the main aspect of the ISO cycle deployment and key lessons learned for further dissemination. We performed the study of the implementation of energy management in the building sector based on the ISO 50001 framework that aims to enhance an organization to pursue the continuous improvement of energy management with a systematic approach. Implementing the plan, do, check and act cycle of the ISO’s framework, it is found that the management keeps a strong commitment to continuous improvement. As part of the energy management system cycle, an Investment Grade Audit (IGA) was performed in 2018. Implementing the IGA recommendation, both passive and active designs have been applied in the Slamet Bratanata building. Active design strategies that have been implemented include building automation system utilization, chiller and lighting replacement and Energy Monitoring System (EMonS) application. Implemented passive designs include windows film installation and an efficient room redesigned for optimizing natural light. To implement the ISO 50001 Energy Management System in the building, the energy management team has also held various activities. It includes developing Standard Operating Procedures, appointing a Person in Charge on each floor, conducting capacity building and performing an energy efficiency campaign. It is estimated that the energy management system has succeeded in reducing energy consumption by 613.188 kWh (in 2018–2020) and the Energy Efficiency Index by 129.06 kWh/m2/year in 2020. Furthermore, management energy implementation also reduced greenhouse gas emissions by 539.60 tons of CO2 equivalent. This study provides a reference for energy management in another building for improving its energy performance.